Digital forensics trends and future - Dezfoli, Farhood Norouzizadeh; Dehghantanha, Ali; Mahmoud, Ramlan; Mohd Sani, Nor Fazlida; Daryabar, Farid (The Society of Digital Information and Wireless Communications, 2013)
Nowadays, rapid evolution of computers and mobile phones has caused these devices to be used in criminal activities. Providing appropriate and sufficient security measures is a difficult job due to complexity of devices which makes investigating crimes involving these devices even harder. Digital forensic is the procedure of investigating computer crimes in the cyber world. Many researches have been done in this area to help forensic investigation to resolve existing challenges. This paper attempts to look into trends of applications of digital forensics and security at hand in various aspects and provide some estimations about future research trends in this area.